PMO-053 Appetite, taste and smell changes after weight loss surgery. (28th May 2012) - Graham, L; Murty, G; Bowrey, D
Abstract : Introduction: It is apparent from day-to-day practice that patients frequently report changes to their appetite, taste and smell after weight loss surgery. There has been surprisingly little written in the literature on this. The aim of the current study was to assess these parameters in a cohort of patients and to explore potential differences between the different types of procedure. Methods: Questionnaires relating to appetite, taste and smell were administered to 264 patients who had undergone weight loss surgery at our institution during the years 2000–2011. Eight of these patients also underwent detailed smell testing using a validated Olfactometer for taste testing for the flavours of sweet, salt, sour and bitter. Results: Responses were received from 133 patients (50%). Sensory changes in appetite, taste and smell were noted by 95%, 68% and 39% of patients respectively. Patients who had undergone Roux-en-Y gastric bypass (RYGB) more frequently experienced new aversions to specific foods compared to patients having other types of surgery (RYGB 73% vs sleeve gastrectomy 40% vs gastric banding 20%), p<0.01. Patients who experienced food aversions experienced a greater level of postoperative weight loss and reduction in BMI, compared to their counterparts without these features. Detailed taste and smell testing did not identify significant changes to smell or taste thresholds after surgery, nor was there a significant correlation between overall taste and smell scores (p=0.67). Conclusion: This study provides preliminary support that patients do experience changes in their appetite, taste and smell following weight loss surgery. These changes need to be investigated further to help support patient education and the informed consent process. Competing interests: None declared.